Translation, cultural adaptation, and validation of the Brazilian Portuguese version of the End-of-Life Professional Caregiver Survey - Garcia, Ana Cláudia Mesquita (2020)
Objectives The aim of this study was to translate, culturally adapt, and psychometrically evaluate the Brazilian version of the End-of-Life Professional Caregiver Survey (BR-EPCS). Method This is an observational cross-sectional study. The sample was composed of 285 Brazilian healthcare professionals who work or worked in the palliative care area. A minimum number of 280 participants were established, following the recommendation of 10 subjects for each instrument item. The European Organisation for Research and Treatment of Cancer - Quality of Life Group Translation Procedure protocol was used for the translation and the cultural adaptation. For the precise/reliable evaluation of factors measured by the BR-EPCS, Cronbach's alpha (a) and composite reliability coefficients were used. The factorial analyses were made by means of the exploratory structural equation modeling methods and confirmatory factor analysis. We have conducted a multiple linear regression analysis to evaluate the sociodemographic variables' capabilities in the result prediction measured by BR-EPCS factors. Results The factorial analysis showed the relevance of two factors: Factor 1 - Given care effectiveness (18 items; Cronbach's a = 0.94; Composite Reliability = 0.95) and Factor 2 - Mourning and ethical and cultural values (10 items; Cronbach's a = 0.89; Composite Reliability = 0.88). Multiple linear regression analyses revealed that the working time, sex, palliative care training, and its own advance directives are predictors of the constructs assessed by the BR-EPCS. Significance of results The BR-EPCS is a reliable, valid, and culturally appropriate tool to identify the educational needs of healthcare professionals who work with palliative care. This instrument can be used for educational and research reasons.